Difference in Cd accumulation among varieties with different growth duration corresponding to typical agro-climate condition in rice ratooning system - Yuan, Shuai; Jiang, Yanfang; Chen, Pingping; Tu, Naimei; Zhou, Wenxin; Yi, Zhenxie (Frontiers in Plant Science, 2024)
The ratoon rice planting area is gradually expanding, but there has been relatively little research on ratoon rice grains contaminated with Cd. In this study, five ratoon rice varieties were selected and divided into three groups according to early-maturity (growth duration: 100–110 days), mid-maturity (growth duration: 110–120 days) and late-maturity (growth duration: 120–130 days ) varieties. Field experiments were done to study the differences in Cd accumulation among ratoon rice varieties with different growth duration. The results showed that the Cd accumulation and concentration of grains spikelet at each growth stage in the main crop were in the order of late-maturity > mid-maturity > early-maturity varieties. However, the trends in Cd concentration and accumulation in grains spikelet during the ratoon crop were the opposite. Analysis found that as the growth duration of the variety extended, the accumulated temperature and daily average temperature in the main crop increased, which significantly increased the translocation factors of Cd from root, stem, and leaf to grains spikelet, and increased the daily average Cd accumulation rate in grains spikelet. The daily average temperature in the ratoon crop increased as the growth duration shortened. The early-maturity variety had higher Cd accumulation in stubble, which promoted the translocation of Cd from the root, stem, and leaf of the plant to the grains spikelet. Therefore, appropriately shortening the growth duration of the main crop and extending the growth duration of the ratoon crop are important ways to reduce Cd accumulation in ratoon rice in areas with mild Cd pollution.